TINDAK PIDANA TERKAIT ASUSILA BERDASARKAN HUKUM PIDANA (KUHP) DI INDONESIA DAN SYARIAT ISLAM DI ACEH (STUDI PENELITIAN DI KOTA BANDA ACEH) - Arivai Nazaruddin Sembiring; Mahmud Mulyadi; Muhammad Ekaputra; Rosnidar Sembiring (USU LAW JOURNAL, 2016)
ABSTRACT Crime related immoral or prostitution Prostitution is a social problem that was and remains in Aceh, prostitution has existed in Aceh which is caused by the economic, sociological, and psychological factors. Although no single regulation which regulates prostitution, from its activity it violates Article 2 of Qanun No. 14/2003 on Khalwat which states that it leads to adultery. Qanun Khalwat states that every action which leads to adultery, such as staying close with someone who is not his muhrim will be punished. On the other hand, the Criminal Code only imposes the sanction on place providers (Article 296) and procuresses (Article 505) while the prostitutes are only given warning and rehabilitated. Qanun No. 14/2003 on Khalwat is only an alternative in punishing the perpetrators in prostitution while conventional law like the Criminal Code only punishes some parts of the perpetrators in prostitution. In Qanun Khalwat, any individual can be punished when he does some action which is categorized as adultery. It is recommended that some elements in Qanun should be included in the Criminal Code in order that any perpetrator in prostitution can be punished. Keywords: Criminal Act in Prostitution, Islamic Sharia, Criminal Code